Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
Jesse Jackson thanking everyone; on stage all standing and applauding: Michael Colvert, Chris Petersen, Rev. Chester Riggins, Lorri Foster, Lily Gonzalez, Barbara Gaines, Aubrey Stone, Pauline Kimber, Jesse Jackson, and Les Kimber